Analisis Strategi Pengembangan Pelabuhan Perikanan Di Nias Utara - Lase, Rosevelt Cerdas; Dawolo, Agnes Juwita; Telaumbanua, Putra Hidayat (Jurnal Perikanan dan Kelautan, 2024)
Government Regulation Number 61 of 2009 concerning Ports, classifies seaports in Indonesia based on a hierarchy consisting of transport ports (PU), collecting ports (PP), feeder ports (PP), consisting of: territorial feeder ports (PR) and territorial feeder ports (PR) and territorial feeder ports (PR). local feeder ports (PL Based on the decision of the Local Feeder Port (PL). In this research using literature study, where this method is a systematic, explicit and reproducible method to identify, bring up and synthesize the works of research results. The purpose of this research is to analyze the Wind Port Development Strategy Analysis of basic facilities, functional facilities and supporting facilities and problems that exist in the Gunungsitoli City Ship Port, analyzing port development The fishing port is very important for fishermen, because it is a point of preservation of land and sea and a place for storage and distribution of goods. In developing the port there must be cooperation between fishermen and communities in the coastal environment and must also be in contact with the government so that it can build a good port in North Nias Regency and get facilities that support the performance of fishermen or coastal communities. fishermen and communities in the coastal environment and must also be in contact with the government so that it can build a good port.